Effects of Internet Language Related to COVID-19 on Mental Health in College Students: The Mediating Effect of Cognitive Flexibility - Wu, Xingzhe; Wang, Zhi; Zhang, Hongpo; Yuan, Peiming; Yu, Quanlei; Zhou, Zhijin; Zhao, Qingbai (Frontiers in Psychology, 2021)
During the COVID-19 pandemic, Internet Language (INL) has extensively influenced daily life. However, the process by which INL influences people’s psychology and behavior is relatively unclear. This study explored the effects of INL on mental health (anxiety and depression). First, we conducted a pilot study to develop a qualified scale about COVID-19 related INL (CINL), which includes two dimensions: frequency and comprehension. This study explored the mediating effect of cognitive flexibility on the relationship between CINL and mental health. Results showed that CINL positively predicted mental health when it was mediated by cognitive flexibility. These results provide a new perspective about cyber behavior, and also have practical significance for interventions on college students’ mental health.